Understanding "Kyphosis" and "Lordosis" for Sagittal Balancing in Two Common Standing Postures. Issue 23 (1st December 2021) - Hey, Hwee Weng Dennis; Lin, Shuxun; Tay, Hui Wen; Tay, Yuan Jie; Liu, Gabriel Ka-Po; Wong, Hee-Kit
Abstract : Study Design: Cross-sectional radiographic comparison study. Objective: The aim of this study was to understand whole-body balancing in directed and natural standing postures, through comparison of kypholordotic ratios on whole-body radiographs of young, healthy subjects. Summary of Background Data: Recent studies highlighted the importance of understanding whole-body balancing, proposing the use of the more physiological natural standing posture, together with the conventional directed standing posture, for imaging. Methods: Sixty healthy, 21-year-old subjects (36 males, 24 females) were recruited. EOS whole-body radiographs of subjects in directed and natural standing postures were obtained. Radiographic parameters compared include C2-sagittal vertical axis (C2-SVA), C7-SVA, C2-7-SVA, global cervical angles (C0-T1 and C2-C7), regional cervical angles (C0-C2, C2-C4, C4-C7), T1-slope, global thoracic angles (T1-T12 and T1-inflection vertebra [Inf]), thoracolumbar angle (T11-L2), global lumbar angles (T12-S1 and Inf-S1), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), spinocoxa angle (SCA), and femoral alignment angle (FAA). Kypholordotic ratios of T1-12/T12-S1, T1-Inf/Inf-S1, Tl-Inf/SCA, and (T1-Inf + FAA)/(T1-slope + SCA) were calculated and compared. Results: Compared to directed standing, natural standing has greater C2-SVA and C7-SVA, more lordotic global and regional cervical angles (except C0-2 angle), higher T1-slope, larger T1- T12 and T1-Inf kyphotic angles, smaller T12-S1 and Inf-S1 lordotic angles, larger PT, more lordotic SCA, and smaller SS and FAA angles. T1-12/T12-S1 and T1-Inf/Inf-S1 ratios in natural standing, and (Tl-Inf + FAA)/(T1-slope + SCA) ratio in both postures approximate 1. There were significant differences between postures for Tl-l2/Tl2-Sl, Tl-Inf/Inf-Sl and Tl-Inf/SCA ratios. Conclusion: Whole-body balancing requires understanding of the balance between kyphosis and lordosis, which varies with the posture of patients. Analysis of kypholordotic ratios obtained in this study allude to the importance of performing whole-body imaging in the directed standing posture, and whole-spine or whole-body imaging in the natural standing posture, so as to fully understand spinal and whole body balancing for spinal realignment surgeries. Level of Evidence: Level 3